WAP-Based Application for Handicrafts Products in Rural Area - Alshomarry, Hani Fawzi Mohsen (2009)
The main objectives of this study are to design WAP-Based Application for Handicrafts products in Rural Area, to develop a prototype of WAP-Based Application for customers to view and search details about the handicraft products in rural area. The design is tested on the prototype and evaluated to test the usability and acceptability of the system. The Wireless Application Protocol (WAP) technologies have been used in this application has enable users to make booking through mobile telephones.